Globalisation and library information networking - Ramamurthy, C. R. (Authorspress, 2004)
Contents of material: Digital libraries in 21st century. ICTs in information services. Globalisation and information liberty. Globalisation and intelligent library services. Information networking. Digital libraries distance learning. Digital information and copyrights issues.